Biodegradation of biodiesel-oil by Cellulosimicrobium sp. Isolated from Colombian Caribbean soils. Issue 18 (10th August 2020) - Bertel-Sevilla, Angela; Cervantes-Ceballos, Leonor; Tirado-Ballestas, Irina; Maldonado-Rojas, Wilson; Alzate-Restrepo, Juan; Olivero-Verbel, Jesus
ABSTRACT: Biodiesel is considered to be a natural substitute for fossil fuel. The comparatively low toxicity of biodiesel and its susceptibility to microbial biodegradation could reduce its environmental impact. Currently, biodiesel is sold previously mixed with petroleum-based hydrocarbons. The aim of this work was to measure the biodegradation potential of commercially available biodiesel, using bacterial strains (BBCOL-001, BBCOL-002, and BBCOL-003) isolated from a tropical forest soils in the Colombian Caribbean. According to nucleotide sequencing of the gene encoding for 16S rRNA, the strains belong to members of the genus Cellulosimicrobium . GC–MS analysis showed that biodiesel-oil alkanes were degraded by an average of 81.5% with optical density reaching 0.2–0.3 in minimal salt media at 37°C for 5 days. Individual diesel-oil alkanes were degraded by the strains at rates between 64.9% to 100%. The increase in bacterial biomass confirmed the use of the substrates by the microorganisms, suggesting these hydrocarbons are a carbon source. Changes in the biochemical behaviour of the strains suggested their capacity to adapt to environmental conditions might be an important resource for bioremediation. GRAPHICAL ABSTRACT: UF0001